On one modulo three mean labeling of graphs. (3rd March 2016) - Jeyanthi, P.; Maheswari, A.; Pandiaraj, P.
Abstract: A graph G is said to be one modulo three mean graph if there is an injective function ϕ from the vertex set of G to the set a | 0≤ a ≤3 q – 2 and either a≡0 (mod 3) or a ≡1 (mod 3) where q is the number of edges of G and ϕ induces a bijection ϕ* from the edge set of G to a | 1≤ a ≤3 q – 2 and either a ≡1 (mod3) given by and the function ϕ is called one modulo three mean labeling of G. In this paper, we show that the graphs and Cm * e Cn are one modulo three mean graphs.